The Mechanistic Differences in HLA-Associated Carbamazepine Hypersensitivity - Gwendolin S. Simper; Lareen S. Gräser; Alexander A. Celik; Joachim Kuhn; Heike Kunze-Schumacher; Gia-Gia T. Hò; Rainer Blasczyk; Andreas Pich; Christina Bade-Doeding (MDPI AG, 2019)
Drug hypersensitivity reactions that resemble acute immune reactions are linked to certain human leucocyte antigen (HLA) alleles. Severe and life-threatening Stevens Johnson Syndrome and Toxic Epidermal Necrolysis following treatment with the antiepileptic and psychotropic drug Carbamazepine are associated with HLA-B*15:02; whereas carriers of HLA-A*31:01 develop milder symptoms. It is not understood how these immunogenic differences emerge genotype-specific. For HLA-B*15:02 an altered peptide presentation has been described following exposure to the main metabolite of carbamazepine that is binding to certain amino acids in the F pocket of the HLA molecule. The difference in the molecular mechanism of these diseases has not been comprehensively analyzed, yet; and is addressed in this study. Soluble HLA-technology was utilized to examine peptide presentation of HLA-A*31:01 in presence and absence of carbamazepine and its main metabolite and to examine the mode of peptide loading. Proteome analysis of drug-treated and untreated cells was performed. Alterations in sA*31:01-presented peptides after treatment with carbamazepine revealed different half-life times of peptide-HLA- or peptide-drug-HLA complexes. Together with observed changes in the proteome elicited through carbamazepine or its metabolite these results illustrate the mechanistic differences in carbamazepine hypersensitivity for HLA-A*31:01 or B*15:02 patients and constitute the bridge between pharmacology and pharmacogenetics for personalized therapeutics.